Maquiagem Corretivo Terapêutica: elaboração e aplicação de um protocolo para saúde mental. - Ruiz, Larissa Pires (2020)
In chronic diseases, such as vitiligo, the patient has restricted, ineffective treatment tools with a few results or without the disease’s remission. It is possible to comprehend the patient’s vulnerability and the vitiligo’s effect, not only for its harmfulness to the individual’s organism, but for its effect over the environment: the aversive stimulations unpredictability produced by cultural matters, rejection reactions, curiosity, prejudice and stigma that leads to anxiety, depression, social isolation and low self-esteem. This study consisted of the elaboration and application of a psychotherapeutic and cosmetic intervention protocol that installed a body of work to increase the participants control over some personal environment variables. This protocol aimed to expand the individual’s available behaviors and reactions for such situations, reduce aversive stimulation and increase the production of pleasant stimulation. The activities included reception, anamnesis, psychoeducation, teaching and training of social skills techniques, self-knowledge, self-perception, self-control, self-esteem, emotional regulation, decision-making, problem-solving, self-care, self-sufficiency, health and dermatological care, cosmetics and self make-up. Its impacts were evaluated in a population of 8 adult women with vitiligo disease, indicatives of the following variables were assessed: 1) living with vitiligo, self-care routine and treatment; 2) physical and mental well-being measures; 3) spots incidence and discomfort; 4) mental health assessments; 5) quality of life assessments; 6) self-esteem assessments; and 7) functional analysis of complaints and identified psychotherapeutic gains. After the procedures application it was observed for all the participants reduction of the depression scores up to 53%, reduction of the social anxiety scores up to 88%, increase of 75% in the self-esteem indicative and gains up to 48,89% in quality of life. More exposed and intimate areas had the higher spot discomfort indicatives; for all of the participants, after the intervention, the discomfort decrease was up to 59%, including all the areas, even those without any physical handling (cosmetic). In general, for all the participants assessed the feedback was of feelings of having more control over the condition and with more tools to live well with vitiligo disease